1B.01: 24 HOUR MODULATION OF PERIPHERAL AND CENTRAL BLOOD PRESSURE, HEART RATE AND ARTERIAL STIFFNESS IN HEART TRANSPLANT HYPERTENSIVE INDIVIDUALS. (June 2015) - Varrenti, M.; Meani, P.; Giupponi, L.; Vallerio, P.; Ferrari, E.; Stucchi, M.; Maloberti, A.; Bruno, J.; Turazza, F.; Parati, G.; Frigerio, M.; Giannattasio, C.
Abstract : Objective: After transplantation heart is denervated, resulting in increased resting heart rate (HR) and altered physiologic response to exercise. In heart transplant (HTX) recipients, absence of blood pressure (BP) dipping phenomenon has been reported, but information on central blood pressure, pulse wave velocity (PWV) and Augmentation Index (Aix) is scanty. Aim of our study was to investigate 24 h modulation not only of brachial BP but also of central-aortic BP (CABPM), HR, PWV and Aix in hypertensive HTX patients. Design and method: We enrolled 24 hypertensive patients, 12 HTX recipients (Ht-HTX), at a mean time after HTX of 10, 4 years, and 12 matched controls (Ht-C). All the patients were clinically stable and had normal LV systolic function. Ambulatory brachial BP, CABPM, PWV and Aix were recorded over 24 hours by Mobilograph device. Results: Baseline brachial and central BP were similar in Ht-HTX vs Ht-C, as were 24 h brachial (128/78 mmHg ± 11/8Vs124/79mmHg ± 14/2) and central BP (119/81 mmHg ± 12/8 vs114/79 mmHg ± 13/7), HR (74.5 ± 11 vs 69 ± 10 bpm), PWV (8.15 ± 1.8 vs 8.2 ± 1.3 m/s) and Aix (23.6 ± 7.5 vs 22.8 ± 5.8%). PWV showed a dipping phenomenon in Ht-C (daily 8.3 ± 1.2, night 7.9 ± 1.4 m/s), p < 0.001) but not in Ht-HTX (daily 8.15 ± 1.8, night 8.15 ± 1.8). This was the case also for HR. Central systolic BP remained unchanged from day to night in Ht-HTX (118 ± 12 vs 119 ± 16 mmHg) but not in Ht-C (117 ± 15 vs 95 ± 33 mmHg), with night central systolic BP being higher in Ht-HTX vs Ht-C (p < 0.05). An index of 24 h variability (standard deviation) of BP and HR was lower in Ht-HTX than in Ht-C, reaching statistical significance only for 24h-HR (4.3 ± 1.7 vs 6.7 ± 2.3, p: 0.01). Conclusions: Our study shows for the first time that in Ht-HTX there is no nocturnal dipping not only of brachial BP and HR but also of CABPM, and PWV up to 10 years after HTX, probably due to persistent cardiac denervation and/or interference by immunosuppressant drugs. Altered autonomic cardiovascular modulation could play a role in the development of restrictive physiology and possibly also of graft vasculopathy.